The need to prepare future teachers to combat homophobia in schools - Johnson, Bernadette Judith (South African Journal of Higher Education, 2016)
Teacher training programmes that improve teachers’ capacity and confidence to address homophobia in schools will engender non-homophobic school contexts. Currently there is a dearth of educational research on future teachers’ preparation for homophobic school contexts. By drawing on group interviews with student teachers, semi-structured interviews with lecturers and course coordinators and analysing course outlines of Lesbian, Gay, Bisexual, Transsexual and Intersex (LGBTI) offerings at three South African universities, this paper shows that such programmes exist, albeit in a limited form. While they enable greater awareness they do not translate into future teachers being enabled to apply their learning in classrooms, school contexts and in their personal lives. It is recommended that more systematic efforts to capacitate teachers for their role in engendering non-homophobic behaviour in schools is needed in teacher training programmes in South African universities.